Pengaruh Kompetensi Pengelola Keuangan, Sistem Pencatatan Keuangan dan Partisipasi Masyarakat Desa terhadap Kinerja Keuangan Badan Usaha Milik Desa: The Influence of Financial Manager Competence, Financial Recording System, and Village Community Participation on the Financial Performance of Village-Owned Enterprises - Andita Sulistyowati; Adityas Wahyuningsih; Farinza Tiara Indani; Dinda Riskanita; Anindita Elladevi (Institut Agama Islam Negeri Kerinci, 2025)
Purpose: This study aims to analyze the influence of financial management competence, financial recording systems, and village community participation on the financial performance of Village-Owned Enterprises (BUMDes). Design/Methodology/Approach: This research employs a quantitative approach using a survey method through questionnaires distributed to 63 respondents from two BUMDes in Ngadirejo Subdistrict, Temanggung Regency. The data were analyzed using multiple linear regression techniques. Findings: The results indicate that financial management competence and financial recording systems have a positive and significant effect on the financial performance of BUMDes. In contrast, village community participation does not have a significant effect on BUMDes financial performance. Research Implications: These findings provide a novel contribution regarding the influence of financial management competence, financial recording systems, and village community participation on the financial performance of Village-Owned Enterprises (BUMDes).